Originals : how non-conformists move the world - Grant, Adam M. (New York : Viking, an imprint of Penguin Random House LLC, 2016)
""Reading Originals made me feel like I was seated across from Adam Grant at a dinner party, as one of my favorite thinkers thrilled me with his insights and his wonderfully new take on the world." --Malcolm Gladwell, #1 New York Times bestselling author of Outliers and The Tipping Point "Originals is one of the most important and captivating books I have ever read, full of surprising and powerful ideas. It will not only change the way you see the world; it might just change the way you live your life. And it could very well inspire you to change your world." --Sheryl Sandberg, chief operating officer of Facebook and #1 New York Times bestselling author of Lean In The New York Times bestselling author of Give and Take examines how people can champion new ideas--and how leaders can encourage originality in their organizations With Give and Take, Adam Grant not only introduced a landmark new paradigm for success but also established himself as one of his generation's most compelling and provocative thought leaders. In Originals he again addresses the challenge of improving the world, but now from the perspective of becoming original: choosing to champion novel ideas and values that go against the grain, battle conformity, and buck outdated traditions. How can we originate new ideas, policies, and practices without risking it all? Using surprising studies and stories spanning business, politics, sports, and entertainment, Grant explores how to recognize a good idea, speak up without getting silenced, build a coalition of allies, choose the right time to act, and manage fear and doubt; how parents and teachers can nurture originality in children; and how leaders can fight groupthink to build cultures that welcome dissent. Learn from an entrepreneur who pitches his start-ups by highlighting the reasons not to invest, a woman at Apple who challenged Steve Jobs from three levels below, an analyst who overturned the rule of secrecy at the CIA, a billionaire financial wizard who fires employees for failing to criticize him, and a TV executive who didn't even work in comedy but saved Seinfeld from the cutting-room floor. The payoff is a set of groundbreaking insights about rejecting conformity and improving the status quo"--
"The New York Times bestselling author of Give and Take examines how people can champion new ideas--and how leaders can encourage originality in their organizations. With Give and Take, Adam Grant not only introduced a landmark new paradigm for success but also established himself as one of his generation's most compelling and provocative thought leaders. In Originals he again addresses the challenge of improving the world, but now from the perspective of becoming original: choosing to champion novel ideas and values that go against the grain, battle conformity, and buck outdated traditions. How can we originate new ideas, policies, and practices without risking it all? Using surprising studies and stories spanning business, politics, sports, and entertainment, Grant explores how to recognize a good idea, speak up without getting silenced, build a coalition of allies, choose the right time to act, and manage fear and doubt; how parents and teachers can nurture originality in children; and how leaders can fight groupthink to build cultures that welcome dissent. Learn from an entrepreneur who pitches his start-ups by highlighting the reasons not to invest, a woman at Apple who challenged Steve Jobs from three levels below, an analyst who overturned the rule of secrecy at the CIA, a billionaire financial wizard who fires employees for failing to criticize him, and a TV executive who didn't even work in comedy but saved Seinfeld from the cutting-room floor. The payoff is a set of groundbreaking insights about rejecting conformity and improving the status quo"--
Includes bibliographical references (pages [259]-308) and index.
Keywords: Creative thinking; Creative ability in business; Organizational change; New products; Entrepreneurship; Success in business; BUSINESS & ECONOMICS / Motivational; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Workplace Culture